The Armenian Diaspora։ Formation in the 1920s - Moskovyan, Lusine (History and Culture, 2026)
The article examines the situation following the Armenian Genocide, when a significant portion of the Armenian population was displaced beyond the borders of their homeland. It presents the ideology of “Spiritual Armenia”, developed by the figures of the Dashnaktsutyun party, as a foundational framework for the consolidation of the Armenian Diaspora. The article also clarifies and analyzes the term “diaspora,” evaluating historians’ perspectives on its evolution within the Armenian context.Additionally, the article provides a comprehensive overview of the distribution and demographic characteristics of the Armenian Diaspora during its formative period in the 1920s.
Keywords: Armenian Genocide; Armenianness; Diaspora; community; Spiritual Armenia; Simon Vratsyan; Garegin Nzhdeh; Middle East; USA